The Strategies and Challenges of English Teachers in Developing Assessment Formative Test? - Lakoro, Suslaningtias (Sebelas Maret University, 2016)
This article purposed to describe the strategies and challenges of English teacher in developing assessment formative test. This study was conducted at SMK Negeri I Gorontalo in the 2014/2015 academic years with six English teachers as the participant. The focus of research is formative test. The study used case study and data collection were obtained from interview to the English teachers as participants of research. The result indicates that teacher strategy mostly used to develop assessment in formative test was objective test, notably multiple choices than essay form. Then, the challenges of developing formative test are various; the lack of resources (teacher handbook) and in service teacher training did not give a detail information or material related to the developing of English assessment. Based on this result, it is recommended that school principals or supervisor give more attention to the English teacher to develop English assessment such as to provide various model of test conducted in several activities such as in service teacher training. Besides, the teacher should be given motivation to do to explore some models of test in many sources.